A Comprehensive Literary Review On The Krimighna (Anthelmintic) Effect Of Shigru (Moringa Oleifera Lam.) In Ayurveda - Das, Srabani; Chattopadhyay, Abichal; Mukherjee, Gopeswar (International Research Journal of Ayurveda & Yoga, 2021)
Ayurveda is one of the world’s oldest medical systems. Since the ancient period, Krimi roga (worm infestations) are still present with worldwide cosmopolitan distribution among different classes. India is widely prevalent Asian country with 60% to 80% estimated cases found in West Bengal, Bihar, Orissa, Punjab, Tamil Nādu and Andhrapradesh.The greater infestations in our country due to improper unhygienic diet and behavior due to illiteracy triggered by environmental and socio-economic status make the burden of severe nutritional deficiencies, anaemia and death. All microorganisms like bacteria, virus, parasite and fungus can be included under the word Krimi. There are several medicinal plants which have been mentioned by the Ayurvedic classics as krimighna or anthelmintic agent, among them Shigru (Moringa oleifera Lam.) is one of the widely used krimighna dravya (Anthelmintic agent) in Ayurveda. So, in present study Shigru has been taken into consideration for its literary review through different classical texts from ancient era to till date. The information regarding its pharmacodynamics as well as procedure of therapeutic uses to be placed here in a methodical manner with the conceptual legitimacy. This review will give an idea about the properties, dosa karma and therapeutic uses of Shigru and the effect of Shigru as krimighna dravya.